Analysis of strut forces for braced excavations in soft clay - Chua, Gabriel Shi Quan (2014)
Due to the constraints of land area in Singapore, there is a need to excavate deeper underground to expand Singapore’s infrastructure. Having a braced system as support prevents the collapse of the excavated soil during work, allowing deep excavation as a result. In this project, the finite element program, Plaxis 2D was used to analyze the forces in the struts for braced excavation in soft clay deposits. The factors examined are the wall stiffness, the depth to the hard stratum, embedment length of the wall, and the soil strength. The result indicates that the soil properties such as undrained shear strength and undrained Young’s modulus are factors that affect the forces in the struts. A decrease of such strength parameters will hence result in higher compression forces within the braced system. The thickness of the soft clay layer, from the final excavated level to the hard stratum shows significant influences on the pressure distribution. The hard stratum below the soft clay layer helps to restrain wall deformation and decrease the forces in the struts.